2022
DOI: 10.1155/2022/7138435
|View full text |Cite
|
Sign up to set email alerts
|

An Atypical Presentation of Pyridoxine-Dependent Epilepsy Diagnosed with Whole Exome Sequencing and Treated with Lysine Restriction and Supplementation with Arginine and Pyridoxine

Abstract: Pyridoxine dependent-developmental and epileptic encephalopathy (PD-DEE) or pyridoxine-dependent epilepsy (PDE) is a rare autosomal recessive disorder caused by biallelic pathogenic variants in ALDH7A1. It classically presents as intractable infantile-onset seizures unresponsive to multiple antiepileptic drugs (AEDs) but with a profound response to large doses of pyridoxine (B6). We report a case of PDE with an atypical clinical presentation. The patient presented at 3 days of life with multifocal seizures, fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In general, patients treated with LRT are reported to have improvements in seizure frequency, behaviour, psychomotor development, speech and biomarkers associated with PDE-ALDH7A1 (Table 1). 14,21,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Two recent studies from the PDE registry data were published. Coughlin et al reported the effect of LRT to the standardised developmental testing scores of 60 patients.…”
Section: Literature Overview Of Treatment Outcome Of Lysine Reduction...mentioning
confidence: 99%
See 1 more Smart Citation
“…In general, patients treated with LRT are reported to have improvements in seizure frequency, behaviour, psychomotor development, speech and biomarkers associated with PDE-ALDH7A1 (Table 1). 14,21,[25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Two recent studies from the PDE registry data were published. Coughlin et al reported the effect of LRT to the standardised developmental testing scores of 60 patients.…”
Section: Literature Overview Of Treatment Outcome Of Lysine Reduction...mentioning
confidence: 99%
“…In general, patients treated with LRT are reported to have improvements in seizure frequency, behaviour, psychomotor development, speech and biomarkers associated with PDE‐ALDH7A1 (Table 1 ). 14 , 21 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 …”
Section: Literature Overview Of Treatment Outcome Of Lysine Reduction...mentioning
confidence: 99%